The Ammonitico Rosso Facies in Sierras Subbéticas UGGp (Córdoba, Spain): Geological Importance and Threats – The Case of La Cañada del Hornillo - Alicia Serna Barquero; Federico Olóriz Sáez; Antonio García Jiménez; Felipe González Barrionuevo (Geoconservation Research, 2021)
The Ammonitico Rosso is one of the most studied as well as most unusual facies developed in the Tethys Ocean, mainly during the Jurassic. This calcareous to marly-calcareous facies was typical on high seabeds seawards from the main platforms and emerged lands, sites where fine sediments accumulated discontinuously, while invertebrate animals tunneled the sea bottom during pauses in deposition. Ammonites are the most common macrofossils. Although a reddish color is characteristic, it is not exclusive. This facies occurs widely in the Sierras Subbéticas UNESCO Global Geopark (Central Betic Cordillera), where four Jurassic–Lower Cretaceous sections have been included in the List of Geological Sites of International Importance, elaborated by the Spanish Geological Survey (IGME), in the frame of the GEOSITES project, as the most representative sites for Ammonitico Rosso facies in Spain. In March 2019, a violation at La Cañada del Hornillo geosite was reported, in which blocks of Ammonitico Rosso facies several cubic meters in size were taken away. At the same time, a recent and illegal construction with the same facies was discovered. The methodology developed to determine the origin of the discovered rocks is analyzed, while a compilation of the information provided by the  Ammonitico Rosso facies studies is presented. This episode promoted a police investigation resulting in the stimulation of the geopark management to adapt its geoconservation strategy, to improve the protection of its geological heritage.